Do Foreign-Owned and U.S.-Owned Establishments Exhibit the Same Location Pattern in U.S. Manufacturing Industries? - Shaver, J. Myles (Journal of International Business Studies, 1998)
There are arguments to support and contradict the proposition that foreign-owned and U.S.-owned establishments exhibit similar location patterns within the United States. This paper addresses these conflicting views by comparing the location of all manufacturing establishments in the United States held by the U.S. and by foreign firms. The empirical evidence indicates that the location patterns of foreign-owned and U.S.-owned establishments differ. Moreover, the most influential factor in explaining the location pattern difference is that foreign-owned establishments, compared to U.S.-owned establishments, favor coastal states. I also find evidence to suggest that foreign firms favor states with low unionization rates, low wage rates, and right to work legislation. These results are consistent with arguments that foreign establishments differ from their domestic counterparts and value location attributes differently.